2015
DOI: 10.1152/ajpheart.00414.2014
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of AMP kinase activation against oxidative stress are associated with prevention of PPARα-cyclophilin D interaction in cardiomyocytes

Abstract: Furthermore, activation of AMPK protects the heart from myocardial infarction and heart failure. The present study examines whether or not AMPK affects the peroxisome proliferator-activated receptor-␣ (PPAR␣)/mitochondria pathway in response to acute oxidative stress in cultured cardiomyocytes. Cultured H9c2 rat embryonic cardioblasts were exposed to H2O2-induced acute oxidative stress in the presence or absence of metformin, compound C (AMPK inhibitor), GW6471 (PPAR␣ inhibitor), or A-769662 (AMPK activator). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 53 publications
1
52
1
Order By: Relevance
“…Mitochondrial short (2 kbp) and long (15 kbp) fragments were used to determine mtDNA damage (Barreto-Torres et al, 2015). Total DNA damage was determined in liver samples by quantifying 8-hydroxy-2′-deoxyguanosine (8-oxo-dG) levels using DNA/RNA Oxidative Damage EIA Kit (Cayman Chemical) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial short (2 kbp) and long (15 kbp) fragments were used to determine mtDNA damage (Barreto-Torres et al, 2015). Total DNA damage was determined in liver samples by quantifying 8-hydroxy-2′-deoxyguanosine (8-oxo-dG) levels using DNA/RNA Oxidative Damage EIA Kit (Cayman Chemical) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…This attenuation proves the antioxidant property of MET [Pintana et al, ; Alzoubi et al, ]. MET activates AMPK, which has a crucial role in stabilizing mitochondrial membrane potential, decreasing endoplasmic reticulum stress along with ROS production consequently avoiding the oxidative damage [Barreto‐Torres et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that oxidative stress induced by H 2 O 2 in H9c2 cardioblasts [122] and in vivo IR in rat hearts [123] stimulates translocation of the peroxisome proliferator-activated receptor alpha (PPARα), a transcription factor and a major regulator of FAO, to the mitochondria and increases its interaction with CypD. The AMPK activators metformin and A-769662 as well as the CypD inhibitor SfA prevented protein–protein interaction between CypD and PPARα and improved cell survival and post-ischemic cardiac recovery [122, 123].…”
Section: Modulation Of Cypd Activitymentioning
confidence: 99%
“…The AMPK activators metformin and A-769662 as well as the CypD inhibitor SfA prevented protein–protein interaction between CypD and PPARα and improved cell survival and post-ischemic cardiac recovery [122, 123]. Although these studies suggest a possible role of the PPARα–CypD interaction to stimulate PTP opening, many questions on the cause-and-effect relationship between these two events remain to be elucidated.…”
Section: Modulation Of Cypd Activitymentioning
confidence: 99%